Novel Carbon Nanotube−Polystyrene Foam Composites for Electromagnetic Interference Shielding - Yang, Yonglai; Gupta, Mool C; Dudley, Kenneth L; Lawrence, Roland W (Nano letters, 2005)
A novel carbon nanotube−polystyrene foam composite has been fabricated successfully. The electromagnetic interference (EMI) shielding effectiveness measurements indicated that such foam composites can be used as very effective, lightweight shielding materials. The correlation between the shielding effectiveness and electrical conductivity and the EMI shielding mechanism of such foam composites are also discussed.